Obtenção de placas a base de pvc reciclado para uso em construção civil - Gentil Junior, Geraldo Ari (2019)
The sustainable development of industrial processes is associated with the post-consumer use of its products. Among the environmental problems is the large production of post-consumer waste from polymeric materials, in particular, Polyvinyl chloride (PVC), used to make garments, sports, construction, etc. On the other hand, the use of wood derivatives can lead to deforestation. Much of the continuous deforestation is driven by the demand for wood used in construction. In addition, part of this wood becomes waste. The development of composite materials, such as plastic wood, is fundamental to guarantee the supply of products to the civil construction sector while taking advantage of industrial and urban waste. Plastic wood may have satisfactory or superior physical, chemical and mechanical characteristics to fully replace the use of wood or plastic. The choice of the use of bamboo in the production of the plates was due to the expectation of adding high resistance to rupture and impact to the product proposed, and motivated by the lack of studies on composite materials with such formation. The objective of this work was to prepare, characterize and economically evaluate plastic wood boards composed of PVCr + wood and PVCr + bamboo waste, in order to use them as components of the civil construction. The boards (17 cm x 17 cm x 1.0 cm) of PVC + wood sawdust and PVC + bamboo were obtained by thermomechanical injection of the blends of materials containing 10, 20, 30 and 40% by weight of vegetable fiber. Dioctyl phthalate (DOP) 1% was used as plasticizer and binder. The injection pressure was 40% (64 tons) and the temperatures in the injection heating zones were 165°C, 160°C, 150°C. Plates samples were obtained for determination of hardness (Shore A), tensile strength and three-point flexural strength (ASTM D790 and ASTM D638). Preliminary results indicated that the addition of vegetal fibers to the recycled PVC reduces tensile strength (up to 60%), but increases flexural strength (up to 550%) and hardness (up to 18%), indicating an excellent potential of recycled PVC boards for use in construction.